2022
DOI: 10.1001/jamapediatrics.2022.0069
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Suicidal Ingestion Among Preadolescent Children From 2000 to 2020

Abstract: Pediatric emergency department visits for suicidality account for more than 1.1 million encounters per year, and this number has doubled in the past decade. Although attention has focused on suicidality among adolescents, another important group to consider is preadolescent children. 1 A recent study of suicide risk screening in the emergency department for children aged 10 to 12 years found that more than half of these children with psychiatric complaints and almost 1 in 10 children with medical complaints re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…The findings of this study agree with those reported for suicide-related calls to PCCs in France during the pandemic, which showed a significant decrease in calls during the initial pandemic months followed by a second phase represented by an increase in calls, primarily involving young females [ 11 ]. Two studies reported an overall increase in pediatric suicides reported to US PCCs between 2000–2020 and 2015–2020, respectively; however, the pandemic period was not specifically compared with the pre-pandemic period, analyses were not done by month, and only percent-changes were calculated [ 7 , 8 ]. In contrast, a study of suicide-related calls to the California Poison Control System revealed a decrease during the pandemic, including among the age group 12–17 years old [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings of this study agree with those reported for suicide-related calls to PCCs in France during the pandemic, which showed a significant decrease in calls during the initial pandemic months followed by a second phase represented by an increase in calls, primarily involving young females [ 11 ]. Two studies reported an overall increase in pediatric suicides reported to US PCCs between 2000–2020 and 2015–2020, respectively; however, the pandemic period was not specifically compared with the pre-pandemic period, analyses were not done by month, and only percent-changes were calculated [ 7 , 8 ]. In contrast, a study of suicide-related calls to the California Poison Control System revealed a decrease during the pandemic, including among the age group 12–17 years old [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Suicide is among the leading causes of death among US youth, and poisoning is a common method of intentional self-harm in this age group [2]. Previous studies have examined suicide trends during the pandemic in the US and other countries [3][4][5][6][7][8][9][10][11][12]. However, these previous studies had limitations, including short pandemic study periods of less than 1 year [6,9], not national in scope [4,12], did not focus on the pediatric age group [5,6,9,11,12], did not specifically compare pre-pandemic and pandemic periods [7,8], did not evaluate monthly trends [5,7,8], examined only emergency department visits [10] or pediatric intensive care unit admissions [3], or lacked more sophisticated analyses such as interrupted time series analysis [4,5,7,8,10,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is more prevalent among adolescents than adults, and several studies have revealed increasing trends in adolescent suicidality over the past decades. [2][3][4][5] In the US National Comorbidity Survey, 12.1% of adolescents reported serious thoughts of suicide, and approximately one-third of those with suicidal ideation attempted suicide before reaching adulthood. 6 Rates of emergency department (ED) visits for intentional self-harm in 2020 were highest among adolescents aged 15 to 19 years compared with older age groups (472 vs 133 per 100 000), 2 and youth suicidal ideation or suicide attempt rates in the US nearly doubled from 2008 to 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Most of them reported loneliness that plays a role in causing their suicidal thoughts. Additionally, mental health stress increased their anxiety and depression [ 6 , 7 , 8 ]. Most of them are male and with 8 to 11 years of schooling level [ 4 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%